Kontradiksi Agama dalam Perspektif Hasipelebeguan Tradisi Mangokal Holi Etnis Batak Toba - Pratiwi, Eka Bella; Harahap, Fazira Ismaillia; Br Siallagan, Putri Sion; Tambunan, Riskida Pitamaro; Siregar, Siti Fadilah Aini (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The